Design and synthesis of electrocatalysts for efficient energy conversion and storage - Tan, Huang (2018)
Efficient energy conversion and storage applications (e.g. liquid fuel cell and water splitting) have been identified as promising solutions to future energy depletion. However, practical installation of energy conversion and storage applications is impeded by the low performance and high cost of electrocatalysts. Therefore, it is imperative to improve the electrocatalysts’ performance so as to decrease the overall cost. The objective of this thesis is to design and synthesize electrocatalysts for energy conversion and storage applications. To this end, several works have been conducted. First, 3D Palladium nanoarchitectures were prepared, with abundant catalytic sites and open space for electrooxidation of formic acid. Second, overpotential for hydrogen evolution was lowered by fabricating two dimensional Co/NC. Third, a hybrid of MOFs was fabricated for introducing synergistic effect towards oxygen evolution. Lastly, a heterostructure of layered double hydroxides was produced for electrochemical oxygen evolution.